X-ray excited luminescence of ytterbium containing YAG single crystalline films - Zakharko, Ya.M.; Luchechko, A.P.; Syvorotka, I.M.; Syvorotka, I.I.; Ubizskii, S.B. (Functional Materials, 2005)
Luminescence properties of ytterbium ions in of У₃AI₅О₁₂ (УAG) epitaxial films have been investigated. The influence of growth conditions on the change of activator ions charge state and the luminescence in visible spectral region has been demonstrated. It has been established that emission bands with maxima at 480 and 580 nm are attributed to the 5d-4f transitions of Уb²⁺ ions. The emission bands with maxima at 330 nm and 500 nm correspond to transitions from charge transfer state to ²F₇/₂ and and ²F₅/₂ state of Уb³⁺ ions, respectively.